Biskyrmion-based artificial neuron. Issue 1 (8th March 2023) - Ribeiro de Assis, Ismael; Mertig, Ingrid; Göbel, Börge
Abstract: Magnetic skyrmions are nanoscale magnetic whirls that are highly stable and can be moved by currents. They have led to the prediction of a skyrmion-based artificial neuron device with leak-integrate-fire functionality. However, so far, these devices lack a refractory process, estimated to be crucial for neuronal dynamics. Here we demonstrate that a biskyrmion-based artificial neuron overcomes this insufficiency. When driven by spin-orbit torques, a single biskyrmion splits into two subskyrmions that move towards a designated location and can be detected electrically, ultimately resembling the excitation process of a neuron that fires. The attractive interaction of the two skyrmions leads to a unique trajectory: Once they reach the detector area, they automatically return to the center to reform the biskyrmion but on a different path. During this reset period, the neuron cannot fire again. Our suggested device resembles a biological neuron with the leak, integrate, fire and refractory characteristics increasing the bio-fidelity of current skyrmion-based devices.